EVALUASI LOAD BALANCING FAILOVER PADA SERVER WEB PEMANTAUAN SUNGAI BERBASIS SENSOR DAN VISUAL MENGGUNAKAN ROUND ROBIN DAN LEAST CONNECTION - Ferry Fachrizal; Sukardi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to evaluate the implementation of failover load balancing on a sensor-based and visual river monitoring web server using the Round Robin and Least Connection algorithms. The system is designed to distribute user requests across multiple backend servers to ensure the service remains stable, responsive, and available in real time. River monitoring data is obtained from sensors and visual cameras and then presented through a web service. Testing was conducted by comparing the performance of the two algorithms based on response time, throughput, availability, downtime, and failover recovery time. The results show that Round Robin is able to distribute requests evenly but is less adaptive to changes in server load. Least Connection provides better performance because it directs requests to the server with the fewest active connections. The failover mechanism also successfully maintains service continuity when one of the servers experiences a failure. Therefore, Least Connection is recommended for river monitoring systems that require high availability and low response time. Keywords: load balancing, failover, Round Robin, Least Connection, web server, river monitoring. Abstrak: Penelitian ini bertujuan untuk mengevaluasi penerapan load balancing failover pada server web pemantauan sungai berbasis sensor dan visual menggunakan algoritma Round Robin dan Least Connection. Sistem dirancang untuk mendistribusikan request pengguna ke beberapa server backend agar layanan tetap stabil, responsif, dan tersedia secara real-time. Data pemantauan sungai diperoleh dari sensor dan kamera visual, kemudian disajikan melalui layanan web. Pengujian dilakukan dengan membandingkan kinerja kedua algoritma berdasarkan response time, throughput, availability, downtime, dan failover recovery time. Hasil penelitian menunjukkan bahwa Round Robin mampu membagi request secara merata, tetapi kurang adaptif terhadap perubahan beban server. Least Connection menghasilkan kinerja lebih baik karena mengarahkan request ke server dengan jumlah koneksi aktif paling sedikit. Mekanisme failover juga berhasil menjaga layanan tetap berjalan ketika salah satu server mengalami gangguan. Dengan demikian, Least Connection lebih direkomendasikan untuk sistem pemantauan sungai yang membutuhkan availability tinggi dan response time rendah. Kata kunci: load balancing, failover, Round Robin, Least Connection, server web, pemantauan sungai.